STUDI KERUNTUHAN BALOK KOMPOSIT BETON BERTULANG YANG MENGANDUNG STYROFOAM - ., SYARIFUDDIN (FORUM BANGUNAN, 2012)
This study aims to analyze the bending behavior of composite reinforced concrete beams containing styrofoam Research done by making test specimens of reinforced concrete beams measuring 15 cm x 20 cm x 250 cm with 12 pieces of test objects consisting three test specimens for each variation of styrofoam 0%, 30%, 40% and 50%. Tests carried out using a loading frame with monotonic loading system by giving two (2) periodic load point with a 1 kN to beam bending collapse. The mechanism of the collapse of the beams have the same pattern.